2009
DOI: 10.1080/17429140802382953
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ectomycorrhizal colonization on the growth and mineral nutrition of Populus deltoides under Aluminum toxicity

Abstract: Aluminum (Al) toxicity has been considered an important factor in limiting the growth and nutrient acquisition of sensitive tree species in acidic soils. Mycorrhizal fungi may offset the negative impacts of Al in the root zone. Here, we report our studies on the effect of Al on the growth and mineral nutrition of Populus deltoides in the presence of the ectomycorrhizal fungus Paxillus involutus. Mycorrhizal and non-mycorrhizal plants were exposed to Al levels of 0, 50, 100 and 200 mg/l for 10 weeks. The biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
2
4
0
Order By: Relevance
“…In this study, all three ECM isolates showed a remarkable ability to improve the growth and Al tolerance of 16-week-old P. massoniana seedlings grown in an acidic yellow soil in the field, even under +Al treatment (Figure 1), which verified that ECM inoculation could improve Al resistance in its host. Similar results were observed for other ECM fungi, including Pisolithus tinctorius and Paxillus involutus, which could improve the Al tolerance of their host plants Eucalyptus [8], Pinus densiflora [9], Populus deltoides [11], and Picea abies [10]. Moreover, Al tolerance conferred by ECM inoculation differed among the ECM isolates, and L. bicolor S238A demonstrated the best Al resistance in P. massoniana seedlings (Figure 1).…”
Section: Aluminum Resistance and Biomass Production In Ecm P Massonisupporting
confidence: 76%
See 3 more Smart Citations
“…In this study, all three ECM isolates showed a remarkable ability to improve the growth and Al tolerance of 16-week-old P. massoniana seedlings grown in an acidic yellow soil in the field, even under +Al treatment (Figure 1), which verified that ECM inoculation could improve Al resistance in its host. Similar results were observed for other ECM fungi, including Pisolithus tinctorius and Paxillus involutus, which could improve the Al tolerance of their host plants Eucalyptus [8], Pinus densiflora [9], Populus deltoides [11], and Picea abies [10]. Moreover, Al tolerance conferred by ECM inoculation differed among the ECM isolates, and L. bicolor S238A demonstrated the best Al resistance in P. massoniana seedlings (Figure 1).…”
Section: Aluminum Resistance and Biomass Production In Ecm P Massonisupporting
confidence: 76%
“…Ectomycorrhizae could ameliorate metal toxicity, partly because these fungi could prevent plants from absorbing metals from the soil [8,11,45,46]. Results from our study provided partial support for this statement (Figure 2d).…”
Section: Accumulation and Translocation Of Al In Ecm P Massoniana Sementioning
confidence: 63%
See 2 more Smart Citations
“…Growth inhibition is an index used extensively for the assessment of Al toxicity (5,36). Numerous studies have demonstrated that various ECM fungi, including L. bicolor (25), P. tinctorius (26,31,37), and P. involutus (38), could enhance plant growth and Al tolerance in acidic culture media. P. tinctorius inoculation also enhanced P. strobus shoot but not root growth with ϩAl treatment (31).…”
Section: Discussionmentioning
confidence: 99%